Autoantibodies Recognizing Secondary NEcrotic Cells Promote Neutrophilic Phagocytosis and Identify Patients With Systemic Lupus Erythematosus - Biermann, Mona H. C.; Boeltz, Sebastian; Pieterse, Elmar; Knopf, Jasmin; Rech, Jürgen; Bilyy, Rostyslav; van der Vlag, Johan; Tincani, Angela; Distler, Jörg H. W.; Krönke, Gerhard; Schett, Georg Andreas; Herrmann, Martin; et al. (Frontiers in Immunology, 2018)
Deficient clearance of apoptotic cells reportedly contributes to the etiopathogenesis of the autoimmune disease Systemic Lupus Erythematosus (SLE). Based on this knowledge we developed a highly specific and sensitive test for the detection of SLE autoantibodies utilizing Secondary NEcrotic Cell (SNEC)-derived material as a substrate. We confirmed the presence of apoptotically modified autoantigens on SNEC (dsDNA, high mobility group box 1 protein, apoptosis-associated chromatin modifications e.g. histones H3-K27-me3; H2A/H4 AcK8,12,16 and H2B-AcK12). Anti-SNEC autoantibodies were measured in the serum of 155 patients with SLE, 89 normal healthy donors (NHD) and 169 patients with other autoimmune connective tissue diseases employing SNEC-based indirect enzyme-linked immunosorbent assay (SNEC ELISA). We compared the test performance of SNEC ELISA with the routine diagnostic tests dsDNA Farr radioimmunoassay (RIA) and nucleosome-based ELISA (anti-dsDNA-NcX-ELISA). SNEC ELISA distinguished patients with SLE with a specificity of 98.9 % and a sensitivity of 70.6 % from NHD clearly surpassing RIA and anti-dsDNA-NcX-ELISA. In contrast to the other tests, SNEC ELISA significantly discriminated patients with SLE from patients with Rheumatoid Arthritis, Primary Anti-Phospholipid Syndrome, Spondyloarthropathy, Psoriatic Arthritis, and Systemic Sclerosis. A positive test result in SNEC ELISA significantly correlated with serological variables and reflected the uptake of opsonized SNEC by neutrophils. This stresses the relevance of SNECs in the pathogenesis of SLE. We conclude that SNEC ELISA allows for the sensitive detection of pathologically relevant autoantibodies, enabling its diagnostic usage. A positive SNEC test reflects the opsonization of cell remnants by autoantibodies, the neutrophil recruitment to tissues and the enhancement of local and systemic inflammatory responses.